2020
DOI: 10.3390/sym12111881
|View full text |Cite
|
Sign up to set email alerts
|

A New Hyperchaotic Map for a Secure Communication Scheme with an Experimental Realization

Abstract: Using different chaotic systems in secure communication, nonlinear control, and many other applications has revealed that these systems have several drawbacks in different aspects. This can cause unfavorable effects to chaos-based applications. Therefore, presenting a chaotic map with complex behaviors is considered important. In this paper, we introduce a new 2D chaotic map, namely, the 2D infinite-collapse-Sine model (2D-ICSM). Various metrics including Lyapunov exponents and bifurcation diagrams are used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 40 publications
0
19
0
Order By: Relevance
“…Yang et al formulated what is called "the cantor fractal" in the logical modifications of the definitions to the subject of local derivatives on fractals. Different studies and applications are indicated in the literature [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al formulated what is called "the cantor fractal" in the logical modifications of the definitions to the subject of local derivatives on fractals. Different studies and applications are indicated in the literature [7][8][9][10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to its three main properties (sensitive dependence on initial condition, positive Lyapunov exponent, and stochasticity and ergodicity), this property makes it highly influential to be widely used in many applications, including biology, physics, economics, and philosophy. In addition to these necessary fields, it also shows a high impact in cryptography due to its ability to generate pseudo-random sequences to be used as keys in the encryption process [11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In this field, these new chaotic maps have been used in real-time applications especially in secure multimedia data communication. For instance, in Al-Saidi et al (2020), a new hyperchaotic map is designed for a secure data communication and successfully implemented on a digital hardware for real-time message data transmission. In another study presented by Ogras and Türk in 2017, the hardware simulation of the chaotic Cubic map was successfully applied in the FPGA environment.…”
Section: Introductionmentioning
confidence: 99%